2020
DOI: 10.4084/mjhid.2021.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nutrition on Disease Severity and Health-Related Quality of Life in Adults With Sickle Cell Disease

Abstract: Background & Aims: Sickle cell disease (SCD has a worldwide distribution and causes significant morbidity and mortality in children and adults. Few studies addressed the determinants of SCD severity in adults; therefore, we investigated the impact of nutrition on the outcome of SCD and health-related quality of life (HRQoL) in adult patients, Methods: In this longitudinal study, we recruited and prospectively followed 62 adults with SCD  (aged ?18 years) for a  median of 93 months. At entry and follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
4
7
0
1
Order By: Relevance
“…A study conducted among hospitalized adult SCD patients in Saudi Arabia revealed lower vitamin B 12 concentrations compared to healthy controls, the degree of deficiency being proportional to severity of disease in the patients. 27 This supports the findings of another study in a Saudi Arabian hospital that reported vitamin B 12 deficiency in nearly half of its SCD patients. 28 In contrast, Kennedy et al found that vitamin B 12 deficiency was rare, and its dietary intake was adequate among hospitalized SCD children in the United States.…”
Section: Discussionsupporting
confidence: 89%
“…A study conducted among hospitalized adult SCD patients in Saudi Arabia revealed lower vitamin B 12 concentrations compared to healthy controls, the degree of deficiency being proportional to severity of disease in the patients. 27 This supports the findings of another study in a Saudi Arabian hospital that reported vitamin B 12 deficiency in nearly half of its SCD patients. 28 In contrast, Kennedy et al found that vitamin B 12 deficiency was rare, and its dietary intake was adequate among hospitalized SCD children in the United States.…”
Section: Discussionsupporting
confidence: 89%
“…Poor nutritional status has been shown to be prevalent in individuals with SCD 35–38 . Limited studies also show that malnutrition and undernutrition affect QoL and are associated with frequent hospitalizations 35,39 . Similarly, our study showed significant associations between nutritional status and worse QoL scores in the pain domains and overall mean QoL score in the SCD cohort.…”
Section: Discussionsupporting
confidence: 75%
“…Body Mass Index is a measure for indicating nutritional status in adults. In the current study, the low BMI of the patients with SCA could be attributable to the increased resting energy expenditure, hypermetabolism, nutrient diversion, and micronutrient deficiencies [ 11 ]. The patients with SCA in our study had lower Mg 2+ and calcium levels, similar to reports by Yousif et al .…”
Section: Discussionmentioning
confidence: 99%